Revisión sistemática de la literatura sobre la microfiltración apical de los cementos selladores Grossman, Sealapex, AH-Plus y MTA, con técnica de obturación lateral entre el año 2015 hasta septiembre del 2020 (2021)
Currently on the market we find various types of cements, some based on epoxy resin, others based on MTA, based on zinc oxide, among many other compounds, therefore the selection of the best sealant cement becomes complex, since all they have very good results and physical-chemical properties ideal for endodontic treatments; in this systematic review drying the studies carried out and published in the last 5 years (2015-2020), focusing the study on the most commercially found sealing cements and most used in general dental practice. This systematic review was carried out qualitatively and not quantitatively, because in the studies found different techniques and measuring instruments were used, only the one with the lowest apical microfiltration and greater penetration into the dentinal tubules was referred to as the most efficient cement, in the information found. in publications. Five sealing cements were compared such as: Grossman, Sealapex, AH-Plus and MTA, performing obturation with the lateral condensation technique, and to which the presence of apical microfiltration was evaluated from least to greatest in each study, resulting in the result of less apical microfiltration of the MTA sealant cement.